The rise of cholesterol testing: how much is unnecessary. - Doll, H; Shine, B; Kay, J; James, T; Glasziou, P (2011)
BACKGROUND: Laboratory testing has increased dramatically over recent decades, which is a consequence particularly of repeat testing or monitoring, as either a response to treatment or follow-up. AIM: To assess rates of measurement of lipid levels (total cholesterol, high-density lipoprotein, triglyceride) for diagnosis and monitoring over the last 20 years. DESIGN OF STUDY: Audit of electronic database. SETTING: A single region in the UK (Oxfordshire). METHOD: Specimens from individual patients were matched over time. All tests that were the third or more in a 3-year period were considered to be for monitoring, while the first and second were considered to be for diagnosis. As recent evidence-based recommendations suggest that frequent monitoring of cholesterol may reflect measurement error rather than true changes, between one and three tests in each 3-year period were considered to be 'necessary'. RESULTS: Over the 20 years from 1987 there has been a more than 15-fold rise in the overall number of lipid tests requested. After a small decline in the early 1990s, testing rose steadily after publication of several large statin trials, particularly tests requested in primary rather than secondary care. Repeat testing (likely to be for monitoring) rose from 24% of tests (1993-1995) to 61% (2005-2007), with between 42% and 79% of tests in 2005-2007 possibly being unnecessary. Mean cholesterol values declined over time from 1996 onwards. CONCLUSION: In the last decade, the number of cholesterol tests performed in Oxfordshire has risen dramatically. Much of this appears to be for monitoring purposes rather than case finding or risk assessment. The majority of cholesterol tests requested may be unnecessary.